The impact of teaching cohesive devices on l2 students’ listening comprehension test scores and language accuracy in written production - Mohammad Nasim, Tahsildar (2015)
The study deals with the integration of grammatical prior knowledge in facilitating L2 students’ listening comprehension. The objective of the current study is to examine the effect of teaching academic text cohesive devices on L2 students’ listening comprehension test scores and to investigate its influence on language accuracy in students’ written production. Based on a pre-post-test research design, 40 students enrolled in English for Academic Purposes course at a university in Malaysia were engaged as participants of the current study. A listening comprehension test was conducted prior to and post-intervention. The intervention consisted of lessons on academic text cohesive devices. The data were analysed and reported using descriptive statistics and paired sample t-tests. From the findings, it is clear that there is an increase in the minimum and maximum scores as well as in the mean scores between the preand post-test scores. More importantly, there is evidently a significant improvement in the participants’ post-test listening comprehension scores as well as in the language accuracy and use of cohesive devices of the L2 students’ written production as compared to the pre-test statistics. In sum, the findings on L2 listening comprehension test scores, language accuracy and noticing confirm that the teaching of academic text cohesive devices to activate prior knowledge does result in significant improvement in L2 listening comprehension, language accuracy and noticing in the written production of the listening text. From these findings two recommendations can be made for the teaching of listening to L2 learners: one; is to recognize the place of grammatical prior knowledge, in this case knowledge of cohesive devices, in enhancing comprehension and language accuracy, and two; listening comprehension can be facilitated through appropriate pre-, while- and post-listening activities